2011
DOI: 10.1186/1475-2875-10-108
|View full text |Cite
|
Sign up to set email alerts
|

Antibody levels to multiple malaria vaccine candidate antigens in relation to clinical malaria episodes in children in the Kasena-Nankana district of Northern Ghana

Abstract: BackgroundConsidering the natural history of malaria of continued susceptibility to infection and episodes of illness that decline in frequency and severity over time, studies which attempt to relate immune response to protection must be longitudinal and have clearly specified definitions of immune status. Putative vaccines are expected to protect against infection, mild or severe disease or reduce transmission, but so far it has not been easy to clearly establish what constitutes protective immunity or how th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
29
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 34 publications
5
29
1
1
Order By: Relevance
“…Previous study conducted in Senegal showed that antibodies level increases with age, specifically in children over 5 years [29]. These results are in line with those found in Ghana that showed IgG levels increased with age [30].…”
Section: Smc Area (N=464) Control Area (N=275) P Valuesupporting
confidence: 82%
“…Previous study conducted in Senegal showed that antibodies level increases with age, specifically in children over 5 years [29]. These results are in line with those found in Ghana that showed IgG levels increased with age [30].…”
Section: Smc Area (N=464) Control Area (N=275) P Valuesupporting
confidence: 82%
“…However other studies did not find a protective effect of antibodies to MSP3 [19], [25], [26] but none of these studies concluded on antibodies to MSP3 appearing as a marker of exposure.…”
Section: Discussionmentioning
confidence: 87%
“…In Ghana, Dodoo and colleagues reported a protective effect of total IgG and IgG subclasses to GLURP (R0 and R2) in the univariate analysis. However neither total IgG nor IgG subclasses to GLURP (R0 and R2) were significantly protective when all the serological covariates were taken into account in the final multivariable model [19], [25]. In a study conducted in Tanzania by Lusingu and colleagues, total IgG to GLURP R0 was not associated with protection against febrile malaria; among IgG subclasses only IgG1 was associated with protection.…”
Section: Discussionmentioning
confidence: 95%
“…Other studies reported that high levels of anti-MSP1 IgG1 antibodies are associated with protection against malaria attacks [50]. A more recent study from Ghana revealed that the risk of clinical malaria decreased with increasing antibody levels against GLURP R2, MSP3, AMA1, MSP1, and EBA175 [51]. However, the number of children with severe anemia was too low to draw conclusions; further studies are needed to confirm that anti-Pf113 antibodies are associated with protection against anemia.…”
Section: Discussionmentioning
confidence: 99%